From SEZs to Thailand 4.0: Geopolitics of borderlands in the Thai state’s vision - Phianphachong Intarat (Forest and Society, 2018)
This article uses the case of Thailand’s two economic policies –the border Special Economic Zones and the Thailand 4.0 model, to explore geopolitics of the Thai-Burmese borderland. It also discuss a theoretical gap in accounting the ways in which the state engages with transnational flows of capital and peoples, and proposes to use the concept of ‘border partial citizenship’ to bridge this gap. It argues that the shift in Thailand’s economic policy portrayed the different ways in which the Thai state envisaged its geographical territory in relations to capital and human mobility. In the border SEZ project, the Thai borderland is a site where the state loosened its relationship with its non-subjects. However, while the border regions seem increasingly opening for migrant mobility, the inner core of the Thai geo-body, a geographical territory that embodies nationhood, is proportionately hyper-sanitized by patriotic discourses of the national advancement in knowledge-based economy and the harsh policy toward undocumented migrant population